Proximity to metro stations and commercial gentrification. (May 2019) - Lin, Jen-Jia; Yang, Shu-Han
Abstract: This study explores the relationship between newly launched metro stations and commercial gentrification. It focuses on gentrifiable areas near five metro stations in Neihu District, Taipei City, Taiwan. Changes in retailers and restaurants located in the study areas from 2009 to 2015 were observed using logit models to analyze the image records of Google Maps Street View. Empirical evidence revealed that the probability of commercial gentrification increases as the travel distance from metro stations decreases. In addition, the influence ranges of commercial gentrification are approximately 240 m for short-term changes (2009–2012) and 300 m for long-term changes (2009–2015). The influence ranges also vary with the land uses of the station areas. Accordingly, this research suggests that local administrations should take commercial gentrification into account when developing metro systems. Highlights: Proximity to a newly-launched metro station induces commercial gentrification. The influence range of metro-induced commercial gentrification geographically extends over time. The influence ranges of metro-induced commercial gentrification vary with the land uses of station areas.